Healthcare System in Saudi Arabia: Evaluating the Impact of Health Policies on Access and Quality of Services – A Scoping Review - Samar alshahat; Razali (Indonesian Journal of Nursing and Health Care, 2025)
Background: The healthcare system in Saudi Arabia has rapidly developed over the past few decades, with the implementation of various policies aimed at improving access to and the quality of healthcare services.Objective: This article is a scoping review that aims to evaluate the impact of health policies on access to and the quality of healthcare services in Saudi Arabia.Methods: By reviewing existing literature, this article identifies key factors influencing access equity, the quality of care, and the ongoing challenges within the country's healthcare system.Results: The findings highlight significant issues, including disparities in access between urban and rural areas, variability in service quality, and reliance on foreign medical professionals.Conclusion: Addressing these challenges is crucial for achieving a more inclusive and sustainable healthcare system in Saudi Arabia. Policymakers must focus on reducing regional disparities, improving healthcare infrastructure, and developing a more self-sufficient medical workforce. Strategic policies and investments will be essential for the continued advancement of the healthcare system and its alignment with Vision 2030.